The role of microglia in adult hippocampal neurogenesis - Gemma, Carmelina; Bachstetter, Adam D. (Frontiers in Cellular Neuroscience, 2013)
Our view of microglia has dramatically changed in the last decade. From cells being “silent” in the healthy brain, microglia have emerged to be actively involved in several brain physiological functions, including adult hippocampal neurogenesis, cognitive and behavioral function. In light of recent discoveries revealing a role of microglia as important effectors of neuronal circuit reorganization, considerable attention has been focused on how microglia and hippocampal neurogenesis could be an interdependent phenomenon. In this review the role of microglia in the adult hippocampal neurogenesis under physiological condition will be discussed.